2019
DOI: 10.1101/644849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered Hippocampal-Prefrontal Neural Dynamics in Mouse Models of Down Syndrome

Abstract: 24 7 These authors contributed equally 25 8 Correspondence: m.walker@ucl.ac.uk 26 27 41 42

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 82 publications
4
1
0
Order By: Relevance
“…Indeed, reduced spike rates and increased tuning in the β-γ-frequency range are both consistent with increased activity of inhibitory neurons ( Atallah et al, 2012 ; Cardin et al, 2009 ; Chen et al, 2017 ; Sohal et al, 2009 ; Veit et al, 2017 ). The overall LFP power spectra observed in mPFC is similar in both Ts and Eu mice, consistently with a recent report ( Chang et al, 2020 ). However, close examination of stLFP revealed a strong increase in the power of β- and low γ-frequency bands during periods of spiking activity.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, reduced spike rates and increased tuning in the β-γ-frequency range are both consistent with increased activity of inhibitory neurons ( Atallah et al, 2012 ; Cardin et al, 2009 ; Chen et al, 2017 ; Sohal et al, 2009 ; Veit et al, 2017 ). The overall LFP power spectra observed in mPFC is similar in both Ts and Eu mice, consistently with a recent report ( Chang et al, 2020 ). However, close examination of stLFP revealed a strong increase in the power of β- and low γ-frequency bands during periods of spiking activity.…”
Section: Discussionsupporting
confidence: 92%
“…An increased hippocampal-mPFC theta coherence was also observed in these animals, which is in agreement with clinical findings showing increased synchrony between neural networks in persons with DS [228,229]. Mouse models of DS also showed altered hippocampal theta-phase modulation of low and high gamma amplitude during rest and behavioral performance [162,163]. Recently, it has been reported that PV basket cells lost their classical fast-spiking phenotype and showed increased excitability in mPFC slices from Ts65Dn mice [164].…”
Section: Electrophysiological Ad-related Phenotypes In Animal Models ...supporting
confidence: 88%
“…Findings from preclinical studies suggest that an early excitation/inhibition imbalance leads to over-inhibition in neural circuits, which may contribute to changes in network activity of DS mouse models [162-164, 226, 227] (Table 1). For example, Dp1Tyb mice showed a general slowing of theta-band oscillations across the hippocampus and medial prefrontal cortex (mPFC), which was associated with slower decision-making in a spontaneous alternation task [162]. An increased hippocampal-mPFC theta coherence was also observed in these animals, which is in agreement with clinical findings showing increased synchrony between neural networks in persons with DS [228,229].…”
Section: Electrophysiological Ad-related Phenotypes In Animal Models ...supporting
confidence: 78%
See 1 more Smart Citation
“…This constellation of evidence leads to the hypothesis that since input to hippocampus from MS is dysfunctional in DS, hippocampal function in TS animals may be abnormal in ways that parallel the changes in human DS that result in deficits in learning and memory. Recent experiments using mouse models of DS strongly suggest spectral phase abnormalities between the hippocampus and prefrontal cortex, and differences in phase-amplitude coupling between theta and gamma in the hippocampus 47 . In these experiments, we use tetrode-based single-unit electrophysiology to record place cells within CA1 of the hippocampus, co-record hippocampal LFP, and examine changes in spectral coherence within the hippocampus that may underlie the central learning and memory deficits in DS.…”
Section: Introductionmentioning
confidence: 99%